Effect of hydrosalpinx on uterine and ovarian hemodynamics in women with tubal factor infertility. (April 2016) - El-Mazny, Akmal; Ramadan, Wafaa; Kamel, Ahmed; Gad-Allah, Sherine
Abstract: Objective: To evaluate the effect of hydrosalpinx on uterine and ovarian blood flows in women with tubal factor infertility. Study design: In a cross-sectional study at a university teaching hospital, 60 women with hydrosalpinx-related tubal infertility (hydrosalpinx group) were compared with 60 women with male or unexplained infertility (non-hydrosalpinx group). In the mid-luteal (peri-implantation) phase of the cycle, endometrial thickness, uterine and ovarian artery pulsatility index (PI) and resistance index (RI), and endometrial and ovarian volume and 3D power Doppler vascularization index (VI), flow index (FI), and vascularization flow index (VFI) were measured in both groups. Results: The endometrial VI ( p  = 0.002), FI ( p  = 0.041), and VFI ( p  = 0.018), and ovarian VI ( p  = 0.011), and VFI ( p  = 0.015) were significantly lower in the hydrosalpinx group than in the non-hydrosalpinx group. However, the endometrial thickness, uterine artery PI and RI, ovarian artery PI and RI, endometrial volume, and ovarian volume and FI were not significantly different between the two groups. Conclusion: Hydrosalpinx is associated with impaired endometrial and ovarian blood flows which may adversely affect endometrial receptivity and oocyte quality.